Le temps des frictions - Jérôme Lamy; Philippe Schäfer (Temporalités)
This article explores the plurivocality of temporalities that is at work in contemporary management. The aim is to understand the relationship that a century-old industrial company has with temporality. Based on a longitudinal case study and a series of interviews conducted within the family business Fleury Michon, the article identifies the discursive mobilizations of different temporalities specific to contemporary capitalism. The logics of the long term (heritage capitalism, local Vendée culture, sustainable development) are required as constitutive elements of the company. In a presentist regime, these temporalities interact, clash and sometimes oppose each other. One of the challenges of management is to produce both a possible conciliation of these temporalities and an euphemization of the power relations that they cannot conceal.